EFEKTIFITAS LEMBAR KEGIATAN SISWA BERBASIS PENDEKATAN PROBLEM SOLVING PADA MATERI PERBANDINGAN SENILAI UNTUK SISWA SMP - Ilfa Febrina Nurismadanti; Euis Eti Rohaeti; Ratna Sariningsih (Journal on Education, 2019)
The purpose of this research is to analyze the feasibility and effectivity of Student Activity Sheets that has been made before actually use while learning process. Methods used i.e. qualitative descriptive with the sample as many as 32 students and three expert people which include learning materials expert, linguist, and media expert. This form of research instruments in question form validation of expert teaching materials, question form validation of linguist, question form validation of media expert, question form of student responses, and Student Activity Sheet based Problem Solving Approach with teaching materials of comparative worth in grade seven. Validation by expert teaching materials amounted to 75%, validation by linguist amounted to 73, 3%, validation by media expert amounted to 96, 3%, student responses amounted to 79, 89%. It means the Student Activity Sheet based Problem Solving Approach that has been made can be used and effective as a learning media.